The complete chloroplast genome of the medicinal plant Polygonum cuspidatum (Polygonaceae) and its phylogenetic implications within the subfamily Polygonoideae. Issue 4 (3rd April 2021) - Ye, Xiaofeng; Lin, Jiuguo; Zhou, Manjia; He, Xiangyu; Yan, Meixiu; Cheng, Rubin
Abstract: Polygonum cuspidatum Siebold & Zucc. is a well-known and widely used medical plant to treat arthritis, gout and inflammation. In this study, we determined the complete chloroplast genome sequence of P. cuspidatum from Zhejiang Province. The assembled chloroplast (cp) genome was 163, 183 bp in length, containing two inverted repeated (IR) regions of 30, 859 bp each, a large single copy (LSC) region of 87, 905 bp, and a small single copy (SSC) region of 13, 560 bp. The genome encodes 131 genes, consisting of 86 protein-coding, 37 tRNA, and eight rRNA genes. The overall GC content of P. cuspidatum is 37.53%, with the highest GC content of 41.27% in the IR region. The 86 protein-coding genes encode 27, 597 amino acids in total, most of which use the initiation codon ATG, except the ndhD gene which starts with ACG. The length of the tRNA genes range from 48 bp to 88 bp, with the highest GC content of 62.16% in tRNA-Arg (ACG) and tRNA-Asp (GUC). A total of 66 simple sequence repeats are identified in the cp of P. cuspidatum. Phylogenetic analysis indicated a sister relationship between P. cuspidatum and Fallopia sachalinensis, suggesting a close genetic relationship between the genera of Polygonum and Fallopia . This work provides basic genetic resources for investigating the evolutionary status and population genetics of this important medicinal species.